Concordance rate between oligoclonal bands and the Kappa index in patients with suspected multiple sclerosis (MS) - Domingues, Renan Barros; Santos, Márcio Vega dos; Salomão, Daiane; Senne, Carlos (Arquivos de Neuro-Psiquiatria, 2024)
Background Oligoclonal bands (OCBs) and Kappa free light chains (FLCs) in the cerebrospinal ﬂuid (CSF) are sensitive markers of intrathecal immunoglobulin (Ig)G synthesis in patients with multiple sclerosis.Objective To evaluate the concordance rate between OCBCs and the Kappa index (KI) in patients with suspected multiple sclerosis (MS).Methods Patients with suspected MS were referred to a specialized CSF laboratory as part of their diagnostic investigation. Paired CSF and serum samples were collected and submitted to detection of OCBs and determination of the KI. Positive and negative results were determined with both methods, and the percentage of agreement between them was established.Results In total, 171 serum and CSF samples from 171 patients were included in the analysis. The mean age of the patients was of 40 ± 14.2 years; 18.9% of them were male, and 81.1% were female. The OCBs and KI presented concordant results in 161 (94.2%) samples: in 74 (43.3%), both were positive, and in 87 (50.9%), both were negative. In 10 cases, the results were discrepant: KI positive/OCB negative in 8 and OCB positive/KI negative in 2 cases.Conclusion The KI and OCBs presented high concordance level. Currently, the detection of OCBs in the CSF is the standard method for MS diagnosis, but it is time-consuming, and its visual interpretation can be difficult. The results suggest that the KI is a good alternative for the detection of intrathecal immunoproduction in cases of suspected MS.
Keywords: Multiple Sclerosis; Immunoglobulin kappa-Chains; Cerebrospinal Fluid; Oligoclonal Bands; Immunoglobulin Light Chains